Human immunodeficiency virus type 1 Rev activation can be achieved without Rev-responsive element RNA if Rev is directed to the target as a Rev/MS2 fusion protein which tethers the MS2 operator RNA. - Venkatesan, S (1992)
The posttranscriptional trans activation of unspliced or partially spliced human immunodeficiency virus RNAs by the Rev regulatory protein is crucial for virus replication and is dependent on sequence-specific RNA binding by Rev. The cognate RNA target of Rev is contained within a highly structured, 244-nucleotide Rev-responsive element (RRE) RNA in the viral env gene. Here, we show that specific interaction with the RRE is not an absolute requirement for Rev function. When the RRE is replaced by a heterologous MS2 phage operator sequence, Rev will facilitate the cytoplasmic expression of human immunodeficiency virus mRNAs containing this sequence if directed to the MS2 operator via the RNA binding motif of the MS2 phage coat protein (MS-C) as a Rev/MS-C fusion protein. Rev/MS-C efficiently activated both RRE and MS2 targets. A mutation in the MS2 operator that abolished the coat protein binding in vitro rendered the mutant RNA nonresponsive to the fusion protein in vivo. Notwithstanding that Rev can be tethered to the viral RNAs via another RNA binding motif, the structural integrity of the N terminus of Rev was still required for optimal trans activation.